Acting, Movements, and the Three Important Components Configuration in Marginalizing Randai as an Entertainment Show (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
The purpose of this research is to reveal how marginalized Randai as a performing art in the life of Minangkabau’s people and their social culture in West Sumatra. This research is based on qualitative methodology with a descriptive method; this research is focused on the marginalization of Randai as the consequences of its lack of acting techniques, movement, and configuration. This research involved traditional artists, dance and Randai artists, indigenous elites, and the people managing the show. Data collection using live monitoring on the Randai performance and doing many interviews related to Randai as an art performance in Minangkabau’s people’s life. Besides that, the data also collected from documentary and literature studies. Data analysis was done using the ethnography method. The results showed that, in reality, the weakness of the Randai show is located on the acting, movement, and its configuration. The weakness of those three key elements is marginalizing the existence of Randai as an art show in social culture life. The lack of acting, movement, and configuration in the performance does not match the current demand of the people.